The International Criminal Court. reflections for a stress test on its foundations - Kowalski, Mateus (2014)
The constitution of the ICC in 2002 represents the ultimate example of the evolution of international criminal justice. The Court is referred to as a paradigmatic institution of the universalist concept of International Law, which envisages an enhanced international public order and which falls within the broader framework of the dominant liberal construct that currently characterizes both International Law and International Relations. However, the criticisms of universalism, in particular as regards the impositions of global liberal institutions and regulatory standards, are also reflected on the ICC. In particular, it has been met with several essential criticisms, such as its dependence on the Security Council, suggesting political interference in a criminal court, or the fact that until now only issues pertaining to Africa have been submitted to the Court, which in turn leads to suspicion about their selectivity. These are the criticisms that undermine the foundations of the ICC. At a time when the Court has not yet concluded any trial, and when there is still some scepticism about the success of its mission, knowing what to expect from the ICC in its task of crime preventing and retribution and building peace depends largely on the strength of its theoretical foundations. It is argued that despite the seemingly solid support discourse rooted in universalism, the answers advanced by this theory are not fully satisfactory due largely to the structural weaknesses that characterise it. This article seeks to offer food for thought on the subject and starts by gauging the competence of legal universalism to support “its” ICC with regard to these issues. It then identifies the aspects that can be addressed in within a more complex context, such as critical theory, which may contribute to the development of a discourse that grants the Court greater theoretical sustainability.